2015
DOI: 10.18061/ojs.v115i2.4607
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Various Caffeine Vehicles on Mood and Cognitive, Neurological and Physiological Functions over Five Hours

Abstract: Although college students’ caffeine consumption has increased over the last decade, studies have not yet determined the time frame in which caffeine exerts its effects nor the impact of the vehicle by which caffeine is consumed. Sixty college students were randomly divided into one placebo (flour) and three caffeine treatment groups: 5-Hour Energy ®, Starbucks DoubleShot ®, or caffeine powder; all dosed at 3 mg caffeine/kg of body weight.  A battery of tests was performed prior to dosing and repeated 2.5 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Caffeine's enhancement of cognitive performance in states of low arousal and sleep deprivation are well documented [14]. In a randomized study of three different caffeine preparations (5-Hour Energy, Starbucks DoubleShot, and 3 mg/kg of caffeine powder) versus placebo, Paulus et al reported that all caffeine groups showed elevations in mood, faster reaction times, and improved cognition [15]. Importantly, doses of more than 200 mg caffeine are often associated with side effects such as insomnia, headaches, tachycardia, and arrhythmia [16,17].…”
Section: Effects Of Caffeinementioning
confidence: 99%
“…Caffeine's enhancement of cognitive performance in states of low arousal and sleep deprivation are well documented [14]. In a randomized study of three different caffeine preparations (5-Hour Energy, Starbucks DoubleShot, and 3 mg/kg of caffeine powder) versus placebo, Paulus et al reported that all caffeine groups showed elevations in mood, faster reaction times, and improved cognition [15]. Importantly, doses of more than 200 mg caffeine are often associated with side effects such as insomnia, headaches, tachycardia, and arrhythmia [16,17].…”
Section: Effects Of Caffeinementioning
confidence: 99%
“…Whereas Kenemans et al (1999) showed caffeine to reduce interference during this task in one of their studies but not the other. Hasenfratz and Battig (1992) reported a reducing effect/improvement of caffeine on the Stroop, and time to complete the task has also been shown to be decreased following caffeine (Patat et al, 2000;Dixit et al, 2012;Pilli et al, 2013;Paulus et al, 2015), whereas Foreman et al (1989 found caffeine to actually increase Stroop interference. This inconsistency in the literature could be caused by the reliability of the task to detect the subtle changes in of a mild stimulant such as caffeine on EF.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous brain waves analysis experiment, the t-test was used to detect the effectiveness of caffeine on brain waves, and the post-test t-test analyzed at 95% confidence level. The results showed significant differences [15]. In another study, Clarke used an independent sample t-test to compare the activity of total power and power for each band in each region, and the θ/β ratio between the subgroup and the control group [10].…”
Section: Data Analysis Processingmentioning
confidence: 99%
“…According to Adam R. Clarke's study, children with attention deficits have low Beta wave activity, and children with hyperactivity disorder have high their Beta wave activity [10]. In other studies, Paulus has demonstrated that caffeine is a psychotropic substance that can stimulate Beta waves [15]. R. Paulus argued that he used caffeine to collect beta waves (13 to 30 Hz) from 60 college students, using 200 mg of caffeine or 60 ml.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation